2020
DOI: 10.1007/s40368-020-00525-x
|View full text |Cite
|
Sign up to set email alerts
|

Validating and assessing the oral health-related quality of life among Hungarian children with cleft lip and palate using Child-OIDP scale

Abstract: Aims To validate the Child-Oral Impact on Daily Performance (Child-OIDP) in the Hungarian language and to explore the oral health-related quality of life (OHRQoL) and associated factors among Hungarian children with cleft lip or/and palate (CLP). Methods This cross-sectional study consists of a survey and clinical examination among conveniently selected children with CLP visiting the Pécs cleft lip and palate clinic, Pécs, Hungary. OHRQoL was assessed using the Hungarian version of Child-OIDP. Additionally, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 29 publications
(39 reference statements)
2
9
0
Order By: Relevance
“…Although it is not yet possible to completely prevent the occurrence of cleft palates, they have a substantial impact on the quality of life of children and adolescents [ 21 , 22 ]. They have major consequences on the jaw structure, aesthetic appearance, speech, eating, and swallowing.…”
Section: Facial Cleftsmentioning
confidence: 99%
“…Although it is not yet possible to completely prevent the occurrence of cleft palates, they have a substantial impact on the quality of life of children and adolescents [ 21 , 22 ]. They have major consequences on the jaw structure, aesthetic appearance, speech, eating, and swallowing.…”
Section: Facial Cleftsmentioning
confidence: 99%
“…Syndromic patients require more attention and support for their multiple potential special needs from both the family and the health care facility, including the cleft teams. [1,[7][8][9][10][11] The percentage of the SCLP patients managed by the PCT was 2.6% during the study. This number is below the 10% and 30% prevalence described in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Syndromic patients require more attention and support for their multiple potential special needs from both the family and the health care facility, including the cleft teams. [ 1 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex and cleft phenotype influence the OHRQoL score. Typically, older ages and female had a higher impact on OHRQoL in CLP patients, but these results are still controversial in the literature [ 9 ]. Moreover, CLP patients can experience lower OHRQoL in physical pain and psychological discomfort domains despite the comprehensive treatment received [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of outcomes related to orthodontic treatment in CLP patients found that quality of life and health resource use are the outcomes with the least representativeness in the literature [ 9 ]. To date, most studies in this field found that surgical patients had a significantly greater reduction in OHRQoL score than patients with severe malocclusions or cleft patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%